Gas Flows in Microsystems - Baldas, Lucien (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The last two decades have witnessed a rapid development of microelectromechanical systems (MEMS) involving gas microflows in various technical fields. Gas microflows can, for example, be observed in microheat exchangers designed for chemical applications or for cooling of electronic components, in fluidic microactuators developed for active flow control purposes, in micronozzles used for the micropropulsion of nano and picosats, in microgas chromatographs, analyzers or separators, in vacuum generators and in Knudsen micropumps, as well as in some organs-on-a-chip, such as artificial lungs. These flows are rarefied due to the small MEMS dimensions, and the rarefaction can be increased by low-pressure conditions. The flows relate to the slip flow, transition or free molecular regimes and can involve monatomic or polyatomic gases and gas mixtures. Hydrodynamics and heat and mass transfer are strongly impacted by rarefaction effects, and temperature-driven microflows offer new opportunities for designing original MEMS for gas pumping or separation. Accordingly, this Special Issue seeks to showcase research papers, short communications, and review articles that focus on novel theoretical and numerical models or data, as well as on new experimental results and technics, for improving knowledge on heat and mass transfer in gas microflows. Papers dealing with the development of original gas MEMS are also welcome.